Pengaruh lingkungan kerja, keterlibatan kerja, dan kohesivitas dalam kelompok kerja terhadap kinerja karyawan dengan kepuasan kerja sebagai variabel mediasi - Sulistyorini, Eri; Sudarmi, Sudarmi; Jati, Eling Purwanto (Performance, 2017)
Purpose: “The Influence of Firm Size, Bid Ask Spread, and Trading Volume on Price Reversal” is a research that aims to analyze the factors that affect price reversal on companies listed in LQ45 Index in period of November 8 - November 16, 2016. Methodology: This research is an associative study to determine the relationship or influence between two or more variables. The population used in this study was all companies listed in the Indonesia Stock Exchange during the study period. The method of collecting data used purposive sampling. Data obtained from purposive sampling method was 44 companies. Analysis method used in this research was multiple linear regression. Testing the hypothesis used the adjusted coefficient of determination, t-statistic test, and f-statistic test. Findings: The result of this research shows that firm size has positive and significant effect to price reversal, bid ask spread has positive and significant effect to price reversal, and trading volume has positive and significant impact to price reversal. Implications: The implications of the above conclusions are that investors can pay attention to the factor of firm size, bid ask spread, and trading volume as a basic for consideration to trade on the exchange to get the best return in accordance with the compensation of the risk that they received. Keywords: firm size, bid ask spread, trading volume, price reversal.